Soft Computing and Medical Bioinformatics - Muppalaneni, Naresh Babu.; Ma, Maode; Gurumoorthy, Sasikumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the applications of soft computing techniques in medical bioinformatics. It reflects the state-of-the-art research in soft computing and bioinformatics, including theory, algorithms, numerical simulations, and error and uncertainty analysis. It also deals with novel applications of new processing techniques in computer science. This book is useful to both students and researchers from computer science and engineering fields.
Cognitive State Classifiers For Identifying Brain Activities -- Classification of Abnormal Blood Vessels in Diabetic Retinopathy using Neural Network -- Design and Implementation of Intelligent System to Detect Malicious Facebook posts using Support Vector Machine (SVM) -- A Novel Evolutionary Automatic Clustering Technique by Unifying Initial Seed Selection Algorithms and K-Means into Teaching-Learning-Based Optimization -- A Novel Level Based Dna Security Algorithm Using DNA Codons -- Construction of Breast Cancer Based Protein Protein Interaction Network Using Multiple Sources of Datasets -- Hybridizing spectral clustering with shadow clustering.
Keywords: Computational intelligence; Medical informatics; Bioinformatics; Biomedical engineering; Computational Intelligence; Health Informatics; Computational and Systems Biology; Biomedical Engineering and Bioengineering